Study of basis-transmitter influence on biopharmaceutical properties of diltiazem nasal dosage form - Gladyshev, V. V.; Kuchina, G. K.; Burlaka, B. S. (Zaporozhye Medical Journal, 2013)
It is set that the type of basis-transmitter has an influence on release of diltiazem from intranasal ointments. Variance analysis of researches results showed that transmitter on the basis of methylcellulose glycerogel provides optimal diltiazem release from intranasal ointments. The second place on intensity of diltiazem release belongs to emulsive basis.